From abnormal to normal—Two tales of growth from 25 years of transition - Torbjörn Becker; Anders Olofsgård (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2017)
In this paper we look at the growth experience of 25 transition countries during the 25 years since the dissolution of the USSR. We find that compared to expectations from a parsimonious growth model the region in the 2000's seems normal in terms of growth performance, i.e. transition in the region is over in this respect. Institutions, speed of reform and macro variables fail to show a stable correlation with (conditional) growth when comparing the early and later periods of transition. We also find that the countries in the former Soviet Union (FSU12), doing substantially worse during the 1990's, in the 2000's are performing better than the 10 countries that joined the EU in 2004 and 2007 (EU10). This is partly explained by rising fuel prices but also point to strong macro forces of mean reversion. Despite this, the gap between the regions is wider in 2015 than in 1991, emphasizing the challenge of making up for deep crises. Finally, the model analysis suggests that looking forward the main challenge for the FSU12 countries (in particular the non-fuel exporters) is to promote more capital investment whereas the main challenge for EU10 is to increase the productivity of existing factors of production.
Keywords: O00; P20; 330; Growth; transition countries; comparative performance; economic crisis; mean reversion